Novel Antennas for UHF RFID Tags: Design and Miniaturization - Anas Sofi; Khalid Roky; Mohammed Bouhorma; Ibrahim Hadj Baraka (International Journal of Electrical and Computer Engineering (IJECE), 2014)
This article focuses of study the nature and characteristics of the antenna, The collective electrical signals acquired from RFID antennas require advanced techniques for feeding, gains and radiation patterns. After an introduction to RFID technology itself (principle and characteristics of different RFID tags), the article offers some examples of applications of this technology in everyday life or in the industry. In order to use radio frequency identification (RFID) antenna for wireless communication and real world applications military and personal communication systems, mobile phones, personal digital assistant (PDA), blue-tooth systems, wireless local area networks (WLAN), road tolling systems, animal traceability etc, studying the nature and characteristics of the antenna is an important use. A novel printed antenna is proposed for Radio Frequency Identification. The antenna has a much wider bandwidth than known printed antenna, mostly planar antennas. The antenna geometry is much smaller than a printed dipole antenna at the same frequency band.DOI:http://dx.doi.org/10.11591/ijece.v4i1.4751